INTEGRATIVE IN SILICO ANALYSIS OF COMMERCIAL SOAP INGREDIENTS FROM NIGERIAN MARKETS PREDICTS POTENTIAL MODULATORS OF HUMAN MELANOGENESIS PATHWAYS - James, Stephen A.; Lawal, Maryam (FUDMA Journal of Sciences, 2026)
Commercial soaps widely sold in African markets contain diverse chemical ingredients that may interact with biological pathways in the skin. However, the potential molecular effects of these compounds on melanogenesis and skin physiology remain insufficiently explored, particularly in populations with darker skin types where melanin provides critical photoprotection. This study applied an integrative bioinformatics approach to evaluate the chemical composition of commonly used soaps sold in Kaduna markets and predict their interactions with proteins involved in pigmentation regulation and skin signaling pathways. Fifteen commercial soap products, including locally manufactured and imported brands, were surveyed. Ingredient profiling identified 43 unique compounds, including surfactants, fatty acids, fragrances, preservatives, pigments, and conditioning agents. Chemical structures retrieved from PubChem were subjected to target prediction using SwissTargetPrediction. Sixteen compounds generated predicted protein targets (probability ≥0.1), yielding 375 potential human protein interactions associated with enzymes, receptors, kinases, and oxidoreductases involved in skin biology. KEGG pathway enrichment revealed significant associations with melanogenesis, tyrosine metabolism, MAPK signaling, PI3K–Akt signaling, and Wnt signaling pathways, which are critical for melanocyte regulation, pigment synthesis, and cellular stress responses. ProTox-3.0 toxicity profiling classified most compounds in Classes IV–VI (harmful to non-toxic), though several ingredients showed potential irritation or sensitization alerts. As a purely computational study without in vitro validation, these predictions require experimental confirmation. Overall, this work demonstrates the utility of computational toxicology and systems bioinformatics for cosmetic ingredient evaluation and offers preliminary insights into how soap constituents may influence pigmentation-related pathways and skin health in darker skin populations.
Keywords: Bioinformatics; Melanogenesis; Soap ingredients; Skin pigmentation; Computational toxicology